Women's Lives Into Print
XX, 238 p.
Keywords: Women's Lives into Print provides a remarkable collection of essays by feminist scholars and writers who focus on the theory, practice and writing of women's auto/biographies. Not only does it foster debate about the reading and interpretation of women's lives, it also explores issues relating to research methodology, and raises questions about the representation of women within feminist auto/biography. Working across a range of subject disciplines, this book comprises a vital and ground-breaking critical text for anyone interested in auto/biography.